Presencia de Dirofilaria immitis en gatos Felis catus en el albergue El Perro Felíz - Briones Vergara, Anyelo Bladimir (2025)
Feline dirofilariasis, an emerging zoonosis caused by Dirofilaria immitis, presents important epidemiological gaps in Ecuador. The present study aimed to determine the prevalence of this infection in cats residing at the “El Perro Feliz” shelter, located in Sucre canton, Manabí province. A non-experimental, exploratory-descriptive study with a mixed approach was conducted; the sample consisted of all 50 cats that permanently inhabit the shelter. For diagnosis, two standard techniques were applied: thick blood smear and Woo test, through the analysis of blood samples obtained by cephalic puncture. Likewise, the feline population was characterized according to demographic and phenotypic variables, with management mainly based on pharmacological prevention and environmental control. Therefore, this plays a key role, as dependence on mosquitoes (Aedes)—the main vector of the disease in this warm area—was a determining factor. Consequently, no microfilariae were detected in any of the samples analyzed using the applied techniques in the evaluated population, leading to the conclusion of absence of infection by Dirofilaria immitis.